Hospital environmental influences and the rate of periprosthetic joint infections at a Canadian tertiary center: a retrospective chart review. Issue 3 (May 2021) - Park, Rosa; Wood, Gavin C.A.; Hopman, Wilma M.; Grant, Heather J.; Yen, David
Abstract : Background: As the demand for total joint arthroplasty is expected to increase substantially in the coming years, the reported incidence of periprosthetic joint infections (PJI) after total joint arthroplasty is also expected to increase. This study investigated both patient factors and hospital factors and their relation to rates of infection for total hip arthroplasty (THA) and total knee arthroplasty (TKA). To the authors' knowledge, this is the first paper to investigate rates of hand washing and carpet removal to PJIs. Methods: Traditional sample size calculations based on effect sizes or differences were not applicable in this observational, retrospective study. The annual rate of irrigation and debridement (I&D) at our institution was calculated. Hospital environmental influences for carpet removal and hand hygiene were obtained from hospital archives. Patient risk factors were obtained from the electronic patient charting system (PCS). Results: The average rate of I&D for THA was 2.8% and TKA was 1.9%. Hospital environmental influences (carpet removal and hand hygiene) were not associated with the rates of I&D. Conclusions: Despite rates of hand hygiene at our institution being reported as having a greater than 90% success rate, we did not find any association between successful hand hygiene practices and rates of PJI. Our study revealed that the rate of infection for THA at our institution was nearly two to three times higher than what was reported in the literature, and we believe poor patient selection played a factor. Level of Evidence: Level III.